1998
DOI: 10.1038/3845
|View full text |Cite|
|
Sign up to set email alerts
|

Mutations in the gene encoding gap junction protein β-3 associated with autosomal dominant hearing impairment

Abstract: Hearing impairment is the most commonly occurring condition that affects the ability of humans to communicate. More than 50% of the cases of profound early-onset deafness are caused by genetic factors. Over 40 loci for non-syndromic deafness have been genetically mapped, and mutations in several genes have been shown to cause hearing loss. Mutations in the gene encoding connexin 26 (GJB2) cause both autosomal recessive and dominant forms of hearing impairment. To study the possible involvement of other members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
235
0
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(242 citation statements)
references
References 14 publications
(7 reference statements)
1
235
0
5
Order By: Relevance
“…The importance of Cxs in hearing has been revealed by genetic studies showing that mutations in Cx genes are among the most common forms of human genetic defects, resulting in hearing impairments in millions of patients with either autosomal dominant or recessive deafness (1)(2)(3). In many ethnic populations, mutations in Cx26 (1,4), Cx30 (5,6), and other Cx genes (7,8) have been linked to approximately half of inherited prelingual nonsyndromic deafness cases. The most commonly found mutations are deletions of either Cx26 (e.g., 35delG or 235delC; refs.…”
mentioning
confidence: 99%
“…The importance of Cxs in hearing has been revealed by genetic studies showing that mutations in Cx genes are among the most common forms of human genetic defects, resulting in hearing impairments in millions of patients with either autosomal dominant or recessive deafness (1)(2)(3). In many ethnic populations, mutations in Cx26 (1,4), Cx30 (5,6), and other Cx genes (7,8) have been linked to approximately half of inherited prelingual nonsyndromic deafness cases. The most commonly found mutations are deletions of either Cx26 (e.g., 35delG or 235delC; refs.…”
mentioning
confidence: 99%
“…Certain mutational alterations of individual connexins are known to be associated with some human hereditary diseases. Thus mutations of Cx32 are associated with Charcot-Marie-Tooth Xlinked peripheral neuropathy (CMTX) (Bergoffen et al, 1993;Nelis et al, 1999;, mutations of Cx26 (White et al, 1998) and Cx31 (Xia et al, 1998) with deafness, and those of Cx31 (Richard et al, 1998) and Cx30 (Lamartine et al, 2000) with skin disorders. It has also been found that autosomal mutations of Cx43 involving phosphorylatable serine or threonine residues in the carboxyl-terminal tail of the protein are associated with complex human heart malformations (Britz-Cunningham et al, 1995).…”
mentioning
confidence: 99%
“…Richard et al [1998a] identified three mutations in the Connexin31 gene (GJB3) in four families with erythrokeratodermia variabilis (EKV). Independently, Xia et al [1998] presented the cloning of the human GJB3 gene on chromosome 1p33-p35 and found mutations in two small deafness families. In both cases the disorders were inherited in an autosomal dominant pattern with partial penetrance (female carriers have either subclinical deafness or normal hearing).…”
Section: Of Gjb2 Mutationsmentioning
confidence: 99%
“…During the last three years 15 of the genes involved in NSHI have been identified by positional cloning or positional candidate gene approaches. Seven genes are responsible for ARNSHI: GJB2 (GDB: 125247; MIM# 121011, 220290, 601544; GenBank: M86849, U43932; URL: http://www.iro.es/ cx26deaf.html) [Kelsell et al, 1997;Zelante et al, 1997], PDS [Li et al, 1998], MYO7A [Liu et al, 1997], MYO15 , TECTA , OTOF [Yasunaga et al, 1999], and GJB3 (GDB: 127820; MIM# 600101, 603324, 133200; GenBank: AF099730, AF052692, AJ004856) [Xia et al, 1998]; 10 for ADNSHI: GJB2 [Kelsell et al, 1997;Denoyelle et al, 1998], HDIA1 [Lynch et al, 1997], MYO7A [Liu et al, 1997], GJB3 [Xia et al, 1998], DFNA5 , TECTA [Verhoeven et al, 1998], COCH [Robertson et al, 1998], POU4F3 [Vahava et al, 1998], KCNQ4 [Kubisch et al, 1999], and GJB6 (GDB: 9958357; GenBank: AJ005585) [Grifa et al, 1999]; one for X-linked non-syndromic hearing impairment: POU3F4 [de Kok et al, 1995]; and one for maternal (mitochondrial) inheritance of non-syndromic hearing loss: 12S rRNA [Prezant et al, 1993;Estivill et al, 1998a] (for details see Hereditary Hearing Loss Homepage).…”
Section: Introductionmentioning
confidence: 99%